Abnormal Bias-Temperature Stress and Thermal Instability of beta-Ga2O3 Nanomembrane field-Effect Transistor - Ma, Jiyeon; Lee, Oukjae; Yoo, Geonwook (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
In this paper, we report on the electrical and thermal instability of beta-Ga2O3 nanomembrane field-effect transistor with a bottom-gate configuration. The fabricated device exhibits high electrical performance of field-effect mobility of up to 60.9 cm(2)/V.s, on/off-current ratio of 10(9), and subthreshold slope of 210 mV/dec. However, we observe abnormal positive threshold voltage (VTH) shifts under negative bias-temperature stress at an elevated operating temperature of 80 degrees C as well as under temperature-dependent transfer characteristics up to 200 degrees C. This abnormal instability is significantly influenced by the surface depletion effect, and is discussed using energy band diagram. The opposite VTH shift was achieved by applying atomic-layer deposited Al2O3 passivation layer.
Keywords: SINGLE-CRYSTALS